MARKETING MIX STRATEGY FOR CORN EMPING PRODUCTS AT UMKM ANTIQUE KITCHEN, OESAPA BARAT URBAN VILLAGE, KELAPA LIMA SUBDISTRICT, KUPANG CITY - Nunuhitu, Yolan; Kapioru, Charles; Bano, Maria (Buletin Ilmiah Impas, 2025)
This study aimed to identify the marketing mix strategy implemented by UMKM Antique Kitchen for its corn emping product and to determine the output of sales improvement influenced by the four elements of the marketing mix, namely product, price, place, and promotion. The study used a mixed methods approach with a sequential explanatory design, in which quantitative analysis was strengthened by qualitative findings. The research was conducted at UMKM Antique Kitchen in Oesapa Barat Urban Village, Kelapa Lima Subdistrict, Kupang City, East Nusa Tenggara. Primary data were collected through observation, interviews, and questionnaires administered to the owner, employees, and consumers, while secondary data were obtained from books, scientific journals, and supporting documents relevant to the marketing activities of the MSME. A total of 50 respondents were involved in the study, and the data were analyzed using descriptive analysis and multiple linear regression supported by classical assumption tests, coefficient of determination, simultaneous F-test, and partial t-test. The results showed that the four elements of the marketing mix had a significant influence on sales improvement. The product strategy focused on maintaining quality, distinctive taste, and attractive packaging; the pricing strategy was adjusted to consumer purchasing power; the place strategy emphasized distribution through local stores, souvenir outlets, and online channels; and the promotion strategy utilized social media and local events. Overall, the implementation of the 4P strategy increased sales to an average of 250 packages per month with income of approximately IDR 11,900,000. The findings indicate that an integrated marketing mix strategy is important for improving competitiveness and sustaining the sales growth of local food-based MSMEs.